MENYAMA BRAYA SEBAGAI PONDASI PRAKTEK MODERASI BERAGAMA MASYARAKAT HINDU-ISLAM DI DESA SERAYA-BUKIT KABUPATEN KARANGASEM - I Ketut Dani Budiantara; Ni Putu Diah Untari Ningsih (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2022)
This study aims to examine and determine (1) the dynamics of social relations between the Hindu and Islamic communities in Seraya-Bukit Village, Karangasem, (2) the views of the Hindu and Islamic communities in Seraya-Bukit Village, Karangasem on the value of menyama braya, and (3) the form of the relationship between menyama braya in social life in Seraya-Bukit Village, Karangasem. This research was carried out in Karangasem by taking samples in Seraya and Bukit villages, areas inhabited by some Hindus and Muslims. This research is categorized as a type of qualitative research, with an empirical approach, which is an approach in which the symptoms to be investigated have existed naturally (real situation). The data in this study were collected by observation or field recording methods, interview methods, and document recording. Data analysis in this study uses the Miles and Huberman model, which in detail describes the data collection, condensation, display and conclusion drawing/verifying. The results of this study are (1) the dynamics of social relations between Hindu and Islamic communities in Seraya-Bukit Village, Karangasem in menyama braya has three reasons that are the basis for continuing to carry out menyama braya in Seraya-Bukit Village, namely historical factors, ideology, and traditions of togetherness. (2) The views of the Hindu and Islamic communities in Seraya-Bukit Village, Kararangasem on the value of Menyama Braya is defined as a social interaction that respects differences in ethnicity, religion and language. Muslims, the teaching of menyama braya is almost the same as the concept of Ukhuwah Islamiyah and Rahmatan Lil Alamin. (3) The form of the Menyama Braya Relationship in Social Life in Seraya-Bukit Village, Karangasem can be explained through several activities as one of the evidences that show this is cultural acculturation between Hindus and Muslims, such as: ngejot, madelokan, mapitulung, magibung, mutual cooperation, use of shared facilities, kebuli, village regulation systems, and use of language. Keywords: menyama braya, religious moderation, Hindu-Islam, Seraya-Bukit village.